Vitamin D Content of Australian Native Food Plants and Australian-Grown Edible Seaweed - Hughes, Laura J. (Nutrients, 2018)
Vitamin D has previously been quantified in some plants and algae, particularly in leaves of the Solanaceae family. We measured the vitamin D content of Australian native food plants and Australian-grown edible seaweed. Using liquid chromatography with triple quadrupole mass spectrometry, 13 samples (including leaf, fruit, and seed) were analyzed in duplicate for vitamin D(2), vitamin D(3), 25-hydroxyvitamin D(2), and 25-hydroxyvitamin D(3). Five samples contained vitamin D(2): raw wattleseed (Acacia victoriae) (0.03 µg/100 g dry weight (DW)); fresh and dried lemon myrtle (Backhousia citriodora) leaves (0.03 and 0.24 µg/100 g DW, respectively); and dried leaves and berries of Tasmanian mountain pepper (Tasmannia lanceolata) (0.67 and 0.05 µg/100 g DW, respectively). Fresh kombu (Lessonia corrugata) contained vitamin D(3) (0.01 µg/100 g DW). Detected amounts were low; however, it is possible that exposure to ultraviolet radiation may increase the vitamin D content of plants and algae if vitamin D precursors are present.